Stewardship Anggaran sebagai Kewajiban Moral: Perspektif Etika Publik atas Efisiensi Belanja Perjalanan Dinas Aparatur Sipil Negara - Julio Kevin Saputra (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This article examines the concept of budget stewardship as a moral obligation inherent to Indonesian civil servants in the management of official travel expenditure. The misuse of official travel—particularly overseas assignments used as supplementary income mechanisms with minimal productive outcomes—reveals a profound ethical crisis within the Indonesian bureaucratic system. Using a qualitative library-research method with a normative-philosophical approach, the study investigates the ethical foundations of budgetary efficiency by drawing on Aristotelian virtue ethics, Kant's categorical imperative and Formula of Humanity, MacIntyre's concept of practices and virtues, Hannah Arendt's theory of the public realm, John Rawls' theory of justice, Denhardt and Denhardt's New Public Service paradigm, and T.H. Marshall's theory of citizenship. The study argues that the misuse of official travel budgets constitutes a moral failure that betrays the public mandate, and that the Indonesian government's regulatory reforms through Presidential Instruction No. 1 of 2025 and the Minister of Home Affairs' Circular of 2026 must be accompanied by more fundamental ethical transformation. The study concludes that the internalisation of stewardship values is an indispensable ethical condition for the realisation of a dignified and just bureaucracy.